Media Representation of Gender Roles : An Analysis of Television and Advertising in Contemporary Society - Maria Petersen; Ida Madsen (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This research examines how television shows and advertising campaigns portray gender roles, focusing on the impact of these portrayals on societal expectations and gender stereotypes. By analyzing popular media content, the study reveals patterns in the depiction of masculinity and femininity, discussing the implications for gender equality and public perception. Findings highlight the need for more balanced representations to challenge traditional stereotypes.